RELATIONSHIP BETWEEN LONG DISTANCE LEARNING HOURS AND STRESS LEVEL OF UKWMS STUDENT DURING COVID-19 PANDEMIC - Steven Bernard; Steven Wijono; Rossy Sintya (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: The COVID-19 pandemic that has hit most countries in the world has forced most countries including Indonesia to adapt to this situation. One example of this adaptation is changing learning methods to distance learning. This learning method has a negative impact on students such as making students stressed. Stress itself is a condition that forces a person to react physically, psychologically and behaviorally to something that has never been experienced or faced and is considered to disturb him and make himself threatened.Objective: To determine the relationship between long distance learning hours and stress levels in UKWMS students during the COVID-19 pandemic.Method: This study is an observational analysis study with a cross sectional approach with a population of 4,050 active UKWMS students class 2018 and 2019. The method used for sampling in this study is non-probability sampling, namely purposive sampling and obtained 106 respondents. Data collection was carried out online using a google form which contained a questionnaire related to distance learning data and the DASS-42 questionnaire to measure the stress level of the respondents. The data obtained were then processed using the Spearman correlation test.Results: Students who took distance learning<6 hours in one day were 19 respondents (18%) and students who took distance learning 6 hours in one day were 87 respondents (82%). The majority of respondents have normal stress levels or not stress. The results of the Spearman correlation test showed p = 0.492 (p>0.05).Conclusion: There is no relationship between long distance learning hours and stress levels.